‘Where does water go’? A critical analysis of nature of water crisis in Darjeeling city, India - Kaberi Koner (SpringerOpen, 2021)
Abstract Water crisis is such a phenomenon that almost every city experiences to some extent these days. Nature, dimensions, and impact of the crisis vary based on spatial diversity. This article attempts to critically analyse the nature of water crisis and to find out the reasons behind such crisis in Darjeeling city. The city’s public water supply is mainly controlled by the municipal authority, and water is supplied from the Senchal lakes. The centralised system, developed by the British in the early nineteenth century, is not sufficient for the entire city at present, and not affordable for all classes as well. Primarily the scarcity emerged due to the city’s population growth, and the city’s changing commercial nature, especially the booming tourism sector. And the age-old water infrastructure cannot cope with the fast-growing demand for water. Moreover, still now municipal authority does not consider a large number of transitory population, while calculating the water demand. Massive gap exists between the actual water scarcity observed in the field and the scarcity shown in the official data. Therefore, a reconsideration of municipal water budget is required to manage water resources and services sustainably. Using both the quantitative and qualitative methods, this empirical study critically assesses the existing gap between demand and supply, and also explores the process of illegal flow of water thus making the scarcity even more intense. It argues for fair and active water governance to minimise the demand–supply gap, and active community participation to ensure water justice to the commons.